Origins of the regulation of honors and distinctions: The case of the province of Cádiz (1950-1975) - Parrilla Amador, Margarita; Pulido Polo, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The use of the protocol is present in history in the Administrations. The main objective of this work tries to make known how the legislation that regulates the awards and that supports public recognition emanates. To respond to this premise, we will resort to the study of cases with the transcription of "circulares" to know the historical evolution of the regulations during the period from 1950 to 1975 in the province of Cádiz. The analysis of the texts will demonstrate how the indications of the General Direction of Local Administration will encourage the creation of special regulations by the municipalities.